Diisocyanate modifiable commercial filter paper with tunable hydrophobicity, enhanced wet tensile strength and antibacterial activity. (15th November 2020) - Zhou, Xuelian; Fu, Yanqiao; Chen, Lidong; Wang, Ruibin; Wang, Xiu; Miao, Yingchun; Ji, Xingxiang; Bian, Huiyang; Dai, Hongqi
Graphical abstract: Highlights: Commercial filter paper was modified with methylene diphenyl diisocyanate. The formation of urethane bonds improved the hydrophobicity and wet tensile strength. The modified paper exhibited antibacterial performance against Escherichia coli . The modified paper is attractive as a substrate to replace the traditional plastics. Abstract: Paper made of cellulose has the advantages of substantial resource, good biocompatibility, large operation scale, and low production cost, however, it is usually hindered to replace plastic due to its inferior stability to water and poor mechanical strength. Herein, commercial filter paper (FP) was reacted with methylene diphenyl diisocyanate (MDI) to fabricate modified paper with tunable hydrophobicity and enhanced wet tensile strength. Due to the formation of urethane linkages in the reaction, both hydrophobicity and wet mechanical properties can be tuned and improved by varying the MDI cross-linking agent, exhibiting highest water contact angle of 137.0° and wet tensile strength of 4.8 MPa. In addition, the modified MDI-FPs exhibited excellent antibacterial performance against Escherichia coli compared with the original FP. Overall, this study provides a more simple approach to modify cellulose paper to produce versatile cellulose-based materials that can potentially replace the non-biodegradable plastics.